Līguma noslēgšanai sekojošas apstākļu būtiskas izmaiņas kā pamats līguma grozījumiem, izbeigšanai vai atcelšanai - Mikoss, Kristaps (Latvijas Universitāte, 2010)
Maģistra darbs veltīts būtisku apstākļu nemainīguma klauzulas (clausula rebus sic stantibus) izpētei, nolūkā novērtēt tās atzīšanas iespējas Latvijas tiesībās. Vispirms tiek analizētas raksturīgākās attieksmes pret apstākļu būtisku izmaiņu institūtu. Šajā nolūkā autors analizē klauzulas izpratni vispārējo tiesību ( Anglija un ASV), Francijas un Vācijas tiesību sistēmās. Tiek secināts, ka izpratne par būtisku apstākļu izmaiņu tiesisko sastāvu ir kopumā līdzīga, taču atšķiras atzītie tiesisko seku veidi. Saglabāt līgumu spēkā, ja vien ir iespējams saprātīgs rezultāts kaut vai daļēji sasniedzot pušu sākotnēji nospraustos mērķus ir vislabākais kompromiss starp tiesiskās drošības un taisnīguma principiem. Tādēļ autora ieskatā no salīdzināmajām tiesību sistēmām vislabākais ir Vācijas tiesību risinājums, kur par primāro tiesiskās aizsardzības līdzekli atzīst prasību par līguma grozīšanu, bet līguma atcelšana vai tā izbeigšana ir alternatīvs tiesiskās aizsardzības līdzeklis gadījumam, kad līguma grozīšana ir nesaprātīga vai neiespējama. Izvērtējot Latvijas tiesu praksi, likumdošanas vēsturi un tiesību doktrīnas atziņas autors secina, ka klauzula kā vispārīgs līgumtiesību princips pagaidām netiek atzīta. Taču vienlaikus eksistē vairākas speciālās normas Civillikumā, kā arī darba, apdrošināšanas un komerctiesībās, kuru tiesiskais sastāvs sevī ietver apstākļu būtiskas izmaiņas. Tiesu praksē un juridiskajā literatūrā ir saskatāmi mēģinājumi paplašināt nepārvaramas varas jēdzienu, kā arī tiek atzīta daļēja līguma izpildes neiespējamība. Tāpat ir skaidrs, ka tiesas principiāli neatbalsta līguma izpildīšanu līdzēju interešu nesamērīguma apstākļos, ko apliecina tiesu prakse lietās par pārmērīgiem līgumsodiem. Minētie apstākļi to kopumā norāda, ka klauzulas doktrīnas atzīšana nākotnē ir iespējama. Analizējot Civillikuma normas tiek secināts, ka klauzula ir atvaisnāma no CL 1. pantā nostiprinātā labas ticības principa un Civillikuma 1779.1 panta normas par līgumisko zaudējumu paredzamību. Darbā ir iekļauti divi likumdošanas priekšlikumi – grozījumi Civillikuma 1776 un 1836 pantos kas regulē neiespējamības tiesiskās sekas, kā arī būtisku apstākļu izmaiņu klauzulas priekšlikums, Civillikuma Saistību daļas pirmās nodaļas piektajā apakšnodaļā (līguma sekas). Analizējot Civillikuma normas tiek secināts, ka faktiskie apstākļi un pieņēmumi par to turpmāko attīstību (darījuma pamats) ir saistīti ar tiesiska darījuma konstitutīvu elementu – darījuma subjektīvo mērķi. Apstākļu izmaiņas, ja vien tās neattiecas uz līdzēja atbildību par risku ir pamats saistības satura izmainīšanai, ko pamato arī CL 1. pantā nostiprinātais labas ticības princips un Civillikuma 1779.1 panta norma par līgumisko zaudējumu paredzamību. Atslēgvārdi: Līgumtiesības, salīdzinošās tiesības, risks, Labas ticības princips, clausula rebus sic stantibus

This paper is devoted to study of regulation of hardship, (or clausula rebus sic stantibus), in order to ascertain the possibility of recognition of it as general principle of Latvian contract law. To compare the solutions of hardship problem author analyzes in depth those jurisdictions, attitudes of which are the most characteristic to the subject: (1) Common law (England and USA), (2) France and (3) Germany. The recognition of matter of fact in jurisdisctions compared is broadly similar, but the legal effect differs. Keeping the contract “alive” wherever it is reasonable, follows both of principles of legal certainity and of good faith and fair dealing. Therefore author suggests, that mosts preferable solution for legal effect of hardship is being offered by German law, where the primary remedy for hardship is adaptation of contract by parties or, when the parties fail to renegotiate the contract, by court. Rescission from or termination of contract is available only as alternate remedy, when disadvantaged party proves, that adaptation of any kind should be impossible or unreasonable. Reviewing the Latvian court practice, legislative history and legal doctrine author concludes that the majority of legal community rejects hardship as a general principle of Latvian contract law. However, there are a number of special provisions in Latvian Civil Code (Civillikums), as well as labor, insurance and commercial law, dealing with hardship situations and permitting not only to rescind but also, whenever it is possible – to modify the contract. There are attempts in court practice and legal writings to broaden the concept of force majeure. It is also clear that Latvian courts generally denies enforcement of the contractual rights which leads to manifestly great disproportion in equality of exchange when dealing with extraordinally high penal clauses in contracts. All these facts taken together may forecast future recognition of hardship doctrine in general part of Latvian contract law. From the provisions of Latvian Civil Code ( Civillikums) author concludes that the principle of hardship can be derived from the principle of good faith the enshrined in Article 1. of Civil Code and provision of predictability of contractual damages (Article 1779.1 ). Consequently, the general principle of hardship is possible to recognize as stemming form provisions mentioned above. The paper includes two legislative proposals: (1) amended articles 1776 and 1836 of Civil Code which regulates the legal consequences of impossibility, and (2) provision for a substantial change of circumstances, proposed to include in fifth subsection (effect of contract) of first part of Part IV of Civil code. Reviewing the Latvian court practice, legislative history and legal doctrine author concludes that the majority of legal community rejects hardship as a general principle of Latvian contract law. However, there are a number of special provisions in Latvian Civil Code (Civillikums), as well as labor, insurance and commercial law, dealing with hardship situations and permitting not only to rescind but also, whenever it is possible – to modify the contract. There are attempts in court practice and legal writings to broaden the concept of force majeure. It is also clear that Latvian courts generally denies enforcement of the contractual rights which leads to manifestly great disproportion in equality of exchange when dealing with extraordinally high penal clauses in contracts. All these facts taken together may forecast future recognition of hardship doctrine in general part of Latvian contract law. From the provisions of Latvian Civil Code ( Civillikums) author concludes that the circumstances which were regarded by both parties as important in time of cocluding the contract (foundation of contract) are are associated with the subjective purpose of the contract, which is one of basic elements required for any legal transaction (tiesisks darījums). As far as
Hardship as a Ground for Adjustment, Termination of or Rescission from Contract
Keywords: Juridiskā zinātne